simplify expression

3(-p)(-2q) i think it is 6pq
my mom thinks its -6pq which is it

3 answers

I agree with you. When you multiply two negative numbers, the product is positive.
how would I check this on my own? I know you put numbers in the place of the letters but when I do that I come up with my moms answer. this is what i have when I check my work. p=-2 q=3
6*(-2)*3 =-36 but 3(-2)(-2*3)=36 could you tell me what i'm doing wrong when I check them pls
3(-p)*(-2q)=(-3p)*(-2q)= 6pq

Becouse product of two negative numbers is positive number.